Multicenter clinical trial of high‐intensity focused ultrasound treatment in glaucoma patients without previous filtering surgery. (7th November 2015) - Aptel, Florent; Denis, Philippe; Rouland, Jean‐François; Renard, Jean‐Paul; Bron, Alain
Abstract: Purpose: To evaluate the efficacy and safety of the ultrasonic circular cyclocoagulation procedure in patients with open‐angle glaucoma naïve of previous filtering surgery. Methods: Prospective non‐comparative interventional clinical study conducted in five French University Hospitals. Thirty eyes of 30 patients with open‐angle glaucoma, intra‐ocular pressure (IOP) > 21 mmHg and with no previous filtering glaucoma surgeries were sonicated with a probe comprising six piezoelectric transducers. The six transducers were activated with a 6‐s exposure time. Complete ophthalmic examinations were performed before the procedure and at 1 day, 1 week, 1, 2, 3, 6 and 12 months after the procedure. Primary outcomes were qualified surgical success (defined as IOP reduction from baseline ≥20% and IOP > 5 mmHg with possible re‐intervention and without hypotensive medication adjunction) and complete surgical success (defined as IOP reduction from baseline ≥20%, IOP > 5 mmHg and IOP < 21 mmHg with possible re‐intervention and without hypotensive medication adjunction) at the last follow‐up visit and vision‐threatening complications. Secondary outcomes were mean IOP at each follow‐up visit compared with baseline, medication use, complications and re‐interventions. Results: Intra‐ocular pressure was significantly reduced ( p < 0.05) from a mean pre‐operative value of 28.2 ± 7.2 mmHg ( n = 3.6 hypotensive medications) to 19.6 ± 7.9 mmHg at 12 months ( n = 3.1 hypotensive medications and n = 1.1 procedures) (mean IOP reduction of 30%). Qualified success was achieved in 63% of eyes (19/30) (mean IOP reduction of 37% in these eyes) and complete success in 46.7% of eyes (14/30) (mean IOP reduction of 37% in these eyes) at the last follow‐up. No major intra‐ or post‐operative complications occurred. Conclusions: The UC 3 procedure seems to be an effective and well‐tolerated method to reduce IOP in patients with open‐angle glaucoma without previous filtering surgery.